x=-2; y=11
Объяснение:
5x+2y=12}
4x+y=3}
Выражаем у через х во втором уравнении: y=3-4x;
Вставляем (3-4x) в первое уравнение вместо у:
5x+2(3-4x)=12;
5x+6-8x-12=0;
-3x-6=0 (умножаем на -1)
3x+6=0;
3x=-6
x=-2
Вставляем -2 в 4x+y=3;
-2*4+y=3;
y=8+3;
y=11.
x=-2; y=11
Объяснение:
5x+2y=12}
4x+y=3}
Выражаем у через х во втором уравнении: y=3-4x;
Вставляем (3-4x) в первое уравнение вместо у:
5x+2(3-4x)=12;
5x+6-8x-12=0;
-3x-6=0 (умножаем на -1)
3x+6=0;
3x=-6
x=-2
Вставляем -2 в 4x+y=3;
-2*4+y=3;
y=8+3;
y=11.